STIM1 and STIM2 cooperatively regulate mouse neutrophil store-operated calcium entry and cytokine production - Clemens, Regina A.; Chong, Joshua; Grimes, Derayvia; Hu, Yongmei; Lowell, Clifford A. (Blood, 2017)
Neutrophils are key effector cells of the innate immune system. Calcium-dependent signaling pathways initiated by store-operated calcium entry (SOCE) are known to regulate neutrophil activation; however, the precise mechanism of this process remains unclear. STIM1 and STIM2 are calcium-sensing molecules that link calcium depletion of the endoplasmic reticulum with opening of plasma membrane calcium channels. Although a role for STIM1 in neutrophil SOCE and activation has been established, the function of STIM2 is unknown. Here we use mice with conditional ablation of Stim1 and/or Stim2 to investigate the role of STIM2 in neutrophil activation. We demonstrate that loss of STIM2 results in decreased SOCE, particularly at lower doses of agonists. Reactive oxygen species (ROS) production, degranulation, and phagocytosis are normal in the absence of STIM2, suggesting STIM1 is the dominant calcium sensor required for classical short-term neutrophil responses. However, neutrophil cytokine production required STIM2, but not STIM1, at least in part as a result of redox regulation of cytokine gene expression. In vivo loss of STIM2 results in lower cytokine levels and protection from mortality in a mouse model of systemic inflammatory response syndrome. These data, combined with previous studies focusing on STIM1, define distinct but cooperative functions for STIM1 and STIM2 in modulating neutrophil bactericidal and cytokine responses. •STIM1 and STIM2 cooperatively regulate neutrophil SOCE.•The interaction of oxidative stress and calcium signaling pathways imparts a specific role for STIM2 in neutrophil cytokine synthesis.